Social media as a strategic capability for startups and the mediating role of social capital - Mumi, Atthaphon (Business: Theory and Practice, 2022)
Social media have been widely adopted in various organizations. The use of social media for achieving business sustainability and financial outcomes has been addressed in the literature. In the entrepreneurship context, social media have received great attention as the platforms can be one of the cost-effective marketing activities and knowledge accumulation. Despite existing evidence regarding the impacts of social media, the study of social media in the startup’s context is limited. Based on the dynamic capabilities perspective, this study relied on data from 128 startups in the emerging economy’s context to investigate the importance of social media for startups. Particularly, the results from PLS-SEM support the significant influence of social media as firm’s strategic capability toward performance. In addition, social capital consisting of three dimensions – cognitive, structural, and relational – has been found to mediate the direct association of social media strategic capability toward the startup performance. This study advances the social media research on entrepreneurship as well as the dynamic capabilities perspective to enhance the startup’s sustainability through enhanced performance. Especially, it encourages the application of social media with the indirect effect of social capital for startups.